The motivators of reading comprehension in the educational process - Ramiro Álvarez Valenzuela; Karla Patricia Heráldez Liera; José Paz Galaviz Rivera; Jesús Francisco Ramírez Gómez; Ana Elizabet Trasviña López; Arturo Trasviña López; Carlos Francisco Berrelleza Gaxiola (Technium Social Sciences Journal, 2024)
Societies require competent individuals, and this is obtained through education. The capabilities are required to produce satisfiers to form a communicated and organized society in all senses. The study of this subject is related to the interest recently shown in society for the issues of education in its basic aspects, such as the lack of motivation that represents important limitations. The complexity of the subject arises from the need for institutions to permanently adapt the internal and external factors that intervene in the formation of readers so that the results can be manifested in society. Some countries do not pay attention to the importance of learning in educational processes, especially as societies face a greater number of difficulties to deal with, while it is important to emphasize that the solution to this issue can create solutions in many other cultural issues, which are always related to issues of high impact. The objective of this research is to analyse the situation of the primary level in reading comprehension, considering the contribution of the educational schemes and the context as important elements. There is a slow level of efficacy in transferring what has been read to other contexts, that is, low levels of text comprehension. The effectiveness of reading comprehension presents the motivational factors, among a great variety, that give it meaning, since it is important to generate the conditions to move the attitude and capabilities in these skills.